Effects of Written and Auditory Language‐Processing Skills on Written Passage Comprehension in Middle and High School Students. Issue 1 (12th October 2015) - Caplan, David; Waters, Gloria; Bertram, Julia; Ostrowski, Adam; Michaud, Jennifer
Abstract: The authors assessed 4, 865 middle and high school students for the ability to recognize and understand written and spoken morphologically simple words, morphologically complex words, and the syntactic structure of sentences and for the ability to answer questions about facts presented in a written passage and to make inferences based on those facts. Factor analysis of combined accuracy and reaction time results for the tests of simple words, complex words, and sentences resulted in three factors in both the auditory and written modalities, reflecting recognition of forms of simple and complex words, understanding of simple and complex words, and recognition of the structure and understanding the meaning of sentences. Structural equation models showed direct effects of these factors in both modalities on written passage comprehension. The results provide evidence that skills in processing language in the written modality are separate from, although related to, skills in auditory language processing and are important determinants of comprehension of written passages in middle and high school.